Publisher Correction: Production of recombinant soluble dimeric C-type lectin-like receptors of rat natural killer cells - Vaněk, Ondřej; Celadova, Petra; Skořepa, Ondřej; Bláha, Jan; Kalousková, Barbora; Dvorská, Anna; Poláchová, Edita; Pucholtová, Helena; Kavan, Daniel; Pompach, Petr; Hofbauerová, Kateřina; Kopecký, Vladimír; et al. (Scientific reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.